Pengaruh Corporate Social Responsibility terhadap Kinerja Keuangan Perusahaan dengan Tata Kelola Perusahaan sebagai Variabel Moderasi pada Perusahaan Manufaktur di Indonesia - Putri Monalisa; Vanica Serly (Jurnal Eksplorasi Akuntansi, 2023)
This study discusses the effect of corporate social responsibility on company financial performance with corporate governance as a moderating variable in manufacturing companies in the consumer good industry sub-sector which are listed on the Indonesia Stock Exchange (IDX) for the 2017-2021 period. The research samples were 29 companies with a total of 145 data. The data analysis technique in this study was using moderated regression analysis (MRA). The results of the study show that corporate social responsibility (CSR) variables have no significant effect on financial performance. Corporate social responsibility (CSR) variable has no significant effect on financial performance which is moderated by corporate governance variables based on foreign ownership, institutional ownership, and managerial ownership. The corporate social responsibility (CSR) variable has a simultaneous or overall effect on financial performance with corporate governance as a moderating variable.